WRF-ARW Numerical Model Sensitivity Test on Simulation of Loud Rain in The South Kalimantan Area - Al Habib, Abdul Hamid; Firdiyanto, Resa Agna (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2023)
On January 13-14, 2021, there was heavy rain in the South Kalimantan region, causing more than 10,000 houses and the main provincial road to be flooded, and also 2 main bridges collapsed. Based on observations at the Syamsudin Noor Meteorological Station Banjarmasin, the rainfall values on January 13 and 14 2021 were 51 mm and 249 mm, respectively. Meanwhile, at the Banjarbaru Climatology Station, it was recorded on January 13-14, 2021, at 45.9 mm and 255.3 mm, respectively. The amount of rainfall recorded at the Banjarmasin Meteorological Station and Banjarbaru Climatology Station makes this condition interesting to study. This simulation uses FNL data with temporal and spatial resolution of 3 hours and 1°×1°, respectively. In this study, the downscaling stage was carried out 2 times with domain 1 of 16 km and domain 2 of 6 km. Furthermore, the input data is running by testing as many as 9 parameterization schemes. Based on the results of the WRF rainfall output with the microphysics scheme (Kessler), the PBL scheme (Yonsei University Scheme) and the cumulus scheme (Kain-Fritcsh) showed the best value and the smallest error value compared to the other 8 schemes. Based on the CAPE value and air humidity, it proves that the atmospheric conditions are unstable and there is significant growth of convective clouds in the South Kalimantan region. The results of the stremaline analysis also show the presence of strong wind bends that result in the accumulation of air masses and indications of orographic rain in the west of the Meratus Mountains.